ANALISIS MOTIVASI INTRINSIK SISWA KELAS IX MADRASAH TSANAWIYAH RIYADHUL HUDA DALAM MENGHAFAL ALFIYAH IBNU MALIK TAHUN 2023 - Nur’azizah, Luthfi; Susiawati, Iis; Utami, Dewi (Cahaya Ilmu Bangsa Institute, 2024)
Intrinsic motivation arises naturally from within an individual and is the primary driving force for someone to actively engage in an activity. Among the classic books in the form of poetry, Alfiyah Ibn Malik is very famous. This book consists of 1002 verses, discussing nahwu-sharaf. Although it seems difficult, memorization is an effective way to understand it. The first problem of this research is what factors influence intrinsic motivation in memorizing Alfiyah Ibn Malik. The second problem is how to build intrinsic motivation in ninth-grade students of MTs Riyadhul Huda in memorizing Alfiyah Ibn Malik. This research uses a qualitative descriptive approach. Data collection was carried out through observation, interviews, and documentation. The results of the study show that students' intrinsic motivation is influenced by a variety of complex and interrelated factors. First, strong intrinsic reasons are the main foundation of students' motivation. A deep desire to master Arabic grammar, understand yellow books, and practice the values in Alfiyah is the main driver. Second, students' positive attitudes, such as enthusiasm and high interest, also play an important role in the memorization process. Third, students' proactive attention, such as setting aside special time for practice, also contributes to their intrinsic motivation. Furthermore, this study also reveals that students' intrinsic motivation can be increased through various efforts. First, self-awareness of each individual's memorization style allows students to develop effective memorization strategies. Second, the competitive spirit towards memorization as an interesting challenge and the existence of clear goals become additional motivation for students. Third, students' interest in Alfiyah as a work of art or song enriches their memorization experience. Keywords: Analysis, Intrinsic Motivation, Memorizing Alfiyah Ibnu Malik